UPAYA MENINGKATKAN HASIL BELAJAR LEMPAR CAKRAM DENGAN MENGGUNAKAN MEDIA MODIFIKASI PIRING PLASTIK - Rambe, Asbir; Haetami, Mimi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the improvement of learning results throwing discs using plastic modification media plates on the students SD Negeri 17 Natai Ilong Sekadau District. Class Action Research Forms. Research subjects were 35 students consisting of 17 female and 18 boys. Data collection techniques used are tests, observations, and questionnaires. Data were analyzed by descriptive analysis and using the mean and percentage formulas. From the results of research conducted can be concluded that the media modification of plastic plates can improve the results of learning throwing discs on the students SD Negeri 17 Natai Ilong Sekadau District. In the first cycle students' learning completeness reached 66% and then increased to 77% in cycle II. This means an increase of 11% in cycle II of cycle I.Keywords: Learning Results Throwing Discs, Media Mods, and Plastic Plates.